A Rare Cause of Childhood Cerebellitis-Influenza Infection: A Case Report and Systematic Review of Literature - Şule Gökçe; Zafer Kurugol; Aslı Aslan (Case Reports in Pediatrics)
Acute cerebellitis is a benign neurologic condition generally caused by viral or bacterial infections. Influenza associated cerebellitis is extremely rare; a 6-year-old boy with acute cerebellitis, who presented with fever, vomiting, weakness, febrile seizure, and acute cerebellar features, is discussed in this article.